A Receptor‐Based Bioadsorbent to Target Advanced Glycation End Products in Chronic Kidney Disease. Issue 6 (11th November 2013) - Zhang, Yangrong; Lapidos, Karen A.; Gal‐Moscovici, Anca; Sprague, Stuart M.; Ameer, Guillermo A.
Abstract The accumulation of advanced glycation end products (AGEs) has been reported to be a major contributor to chronic systemic inflammation. AGEs are not efficiently removed by hemodialysis or the kidney of a chronic kidney disease (CKD) patient. The goal of this study was to develop a receptor for AGEs (RAGE)‐based bioadsorbent device that was capable of removing endogenous AGEs from human blood. The extracellular domain of RAGE was immobilized onto agarose beads to generate the bioadsorbent. The efficacy of AGE removal from saline, serum, and whole blood; biological effects of AGE reduction; and hemocompatibility and stability of the bioadsorbent were investigated. The bioadsorbent bound AGE‐modified bovine serum albumin (AGE‐BSA) with a binding capacity of 0.73 ± 0.07 mg AGE‐BSA/mL bioadsorbent. The bioadsorbent significantly reduced the concentration of total AGEs in serum isolated from end‐stage kidney disease patients by 57%. AGE removal resulted in a significant reduction of vascular cell adhesion molecule‐1 expression in human endothelial cells and abolishment of osteoclast formation in osteoclast progenitor cells. A hollow fiber device loaded with bioadsorbent‐reduced endogenous AGEs from recirculated blood to 36% of baseline levels with no significant changes in total protein or albumin concentration. The bioadsorbent maintained AGE‐specific binding capacity after freeze‐drying and storage for 1 year. This approach provides the foundation for further development of soluble RAGE‐based extracorporeal therapies to selectively deplete serum AGEs from human blood and decrease inflammation in patients with diabetes and/or CKD.